68Ga-PSMA-11 PET/CT in newly diagnosed carcinoma of the prostate: correlation of intraprostatic PSMA uptake with several clinical parameters - Körber, Stefan A.; Kratochwil, Clemens; Kesch, Claudia; Häfner, Matthias; Katayama, Sonja; Mier, Walter; Herfarth, Klaus; Haberkorn, Uwe; Debus, Jürgen; Giesel, Frederik L. (Journal of nuclear medicine, 2017)
68Ga-prostate-specific membrane antigen (PSMA) PET/CT is a promising diagnostic tool for patients with prostate cancer. Our study evaluates SUVs in benign prostate tissue and malignant, intraprostatic tumor lesions and correlates results with several clinical parameters. Methods: One hundred four men with newly diagnosed prostate carcinoma and no previous therapy were included in this study. SUVmax was measured and correlated with biopsy findings and MRI. Afterward, data were compared with current prostate-specific antigen (PSA) values, Gleason score (GS), and d’Amico risk classification. Results: In this investigation a mean SUVmax of 1.88 ± 0.44 in healthy prostate tissue compared with 10.77 ± 8.45 in malignant prostate lesions (P < 0.001) was observed. Patients with higher PSA, higher GS, and higher d’Amico risk score had statistically significant higher PSMA uptake on PET/CT (P < 0.001 each). Conclusion: PSMA PET/CT is well suited for detecting the intraprostatic malignant lesion in patients with newly diagnosed prostate cancer. Our findings indicate a significant correlation of PSMA uptake with PSA, GS, and risk classification according to the d’Amico scale.
Im Titel ist "68" vor Ga-PSMA-11 hochgestellt
Gesehen am 05.11.2018